International migration as occupational mobility - Dean R. Lillard; Anna Manzoni (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
We investigate whether Germans immigrants to the US work in higher-status occupations than they would have had they remained in Germany. We account for potential bias from selective migration. The probability of migration is identified using life-cycle and cohort variation in economic conditions in the US. We also explore whether occupational choices vary for Germans who migrated as children or as adults. Our results allow us to decompose observed differences in occupational status of migrants and non migrants into the part explained by selection effects and the part that is causal, extending the literature on international migration.
Keywords: J24; J61; J62; 330; Internationale Wanderung; Migranten; Deutsche; Erwerbsverlauf; Arbeitsmobilität; Schätzung; USA